Michele Renee Salzman, Marvina A. Sweeney & William Adler (eds.), The Cambridge History of Religions in the Ancient World (2 vols.) (New York: Cambridge University Press, 2013) - Giorgio Baruchello (Nordicum-Mediterraneum, 2014)
Review of: Michele Renee Salzman, Marvina A. Sweeney & William Adler (eds.), The Cambridge History of Religions in the Ancient World (2 vols.) (New York: Cambridge University Press, 2013)